Preparation method and application of Ce-based high-entropy nitrogen oxide material

The preparation of Ce-based high-entropy nitrogen oxide materials through dissolution-polymerization-calcination-nitriding method solves the problem of high preparation temperature in the prior art, realizes low-temperature preparation and efficient catalysis, and meets the application needs of high-entropy nitrogen oxide materials in the catalysis field.

CN119873764AActive Publication Date: 2025-04-25DALIAN MARITIME UNIVERSITY

Patent Information

Application Number
CN202411939597.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-25
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing high-entropy nitrogen oxide preparation technology has problems of high temperature and high equipment requirements, and the application potential of high-entropy nitrogen oxide materials in the catalysis field has not been fully utilized.

Method used

By regulating the order of addition of precursors and dissolution temperature, the HE metal salt, titanium precursor and citric acid are uniformly mixed, and the heating gelation treatment is performed, followed by heat treatment and nitriding treatment to prepare Ce-based high-entropy nitrogen oxide material.

Benefits of technology

The preparation of high-entropy nitrogen oxide materials is realized at low temperature, which simplifies the preparation process, improves the controllability and universality of the materials, and provides multifunctional active sites for catalytic reactions to regulate the electronic characteristics of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873764A_ABST
    Figure CN119873764A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high-entropy materials, and particularly relates to a preparation method and application of a Ce-based high-entropy nitrogen oxide material. The method comprises the following steps: (1) dissolving a titanium precursor in ethylene glycol, and adding HE metal salt and citric acid to obtain a mixed solution; (2) heating the mixed solution obtained in the step (1) to obtain a gel precursor; (3) carrying out heat treatment on the gel precursor obtained in the step (2); and (4) carrying out nitrogen treatment on the powder obtained in the step (3) by utilizing ammonia gas to obtain the high-entropy nitrogen oxide material. The metal types in the prepared high-entropy nitrogen oxide material are easy to modulate, the preparation method is simple and controllable, the preparation conditions are mild, and the high-entropy nitrogen oxide material has universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high entropy materials, and in particular relates to a preparation method of a Ce-based high entropy oxynitride material and application thereof. Background Art

[0002] As a new type of material, high entropy materials have attracted widespread attention in recent years. The concept of high entropy was originally developed from high entropy alloys. It was first proposed by Professor Ye Junwei in 2004 and then gradually expanded to other material systems. At present, this type of material mainly refers to single-phase alloys or solid solution materials containing four or more components with similar element contents (Science, 2022, 376, eabn3103; Sci. Adv., 2021, 7, eabg1600; J. Mater. Chem. A, 2020, 8, 3814-3821). High entropy materials have the characteristics of diverse and adjustable components and exhibit four unique effects, including high entropy effect, lattice distortion effect, hysteresis diffusion effect and cocktail effect, which make them show great application potential in materials, energy, environment, catalysis and other fields.

[0003] Perovskite oxynitride materials have wide-spectrum visible light response capabilities and show excellent performance in the fields of solar energy utilization and catalysis (J.Am.Chem.Soc.,2012,134,20,8348-8351; Adv.Mater.,2021,33,2101883; Nat.Commun.,2021,12,1005). However, the synthesis process of oxynitrides often requires high temperature conditions, which places high demands on synthesis equipment. In particular, Ce-based oxynitrides, such as CeTiO2N, need to be calcined at 1200°C in a platinum boat for 8 hours and then nitrided at 950°C for 20 hours to be synthesized (Chem.Mater.,2015,27,2414-2420). The unique effect of high-entropy oxynitride materials can not only reduce the preparation temperature, but also provide multifunctional active sites for complex catalytic reactions through multi-element synergy, regulate the electronic properties of the material, and thus lay the foundation for the precise regulation of catalytic activity and selectivity. However, the current preparation technology of high-entropy nitrogen oxide materials is very limited. The development of new high-entropy nitrogen oxide material preparation technology still faces great challenges. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of Ce-based high entropy oxynitride materials in order to solve the above problems.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] On the one hand, the present invention provides a method for preparing a Ce-based high-entropy oxynitride material, wherein the chemical composition formula of the oxynitride material is HETiO2N, wherein HE is a combination of Ce and at least four of La, Sm, Pr, Nd, Gd, Yb, Tb, Eu, Ho, Er, Tm, Lu, and Dy; and the percentage of the molar number of each HE metal element to the total molar number of all HE metal elements is 5% to 35%.

[0007] The method comprises the following steps:

[0008] (1) dissolving a titanium precursor in ethylene glycol, adding HE metal salt and citric acid to obtain a mixed solution;

[0009] (2) heating the mixed solution obtained in step (1) to obtain a gel precursor;

[0010] (3) heat treating the gel precursor obtained in step (2);

[0011] (4) The powder obtained in step (3) is nitrided using ammonia gas to obtain the high entropy nitrogen oxide material.

[0012] In the above technical solution, further, in step (1), the molar ratio of citric acid to all metals is 2:1 to 6:1;

[0013] The molar ratio of ethylene glycol to all metals is 10:1 to 30:1;

[0014] The molar ratio of the HE metal to Ti is 1:1.

[0015] In the above technical solution, further, in step (1), the HE metal salt is a nitrate, acetate or chloride of HE;

[0016] The titanium precursor is one of tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate.

[0017] In the above technical solution, further, in step (2), the heating temperature is 110 to 160° C., and the insulation time is 3 to 18 hours.

[0018] In the above technical solution, further, in step (3), the heat treatment is firstly heated to 300-350°C, maintained for 1-3 hours, and then heated to 600-1000°C, maintained for 1-5 hours.

[0019] In the above technical solution, further, in step (3), the atmosphere of the heat treatment is hydrogen or a mixture of hydrogen and argon.

[0020] In the above technical solution, further, in step (4), the nitriding temperature is 800 to 1200° C., and the insulation time is 1 to 5 hours.

[0021] Another aspect of the present invention provides an application of the high entropy nitrogen oxide material in a photocatalytic reaction.

[0022] The present invention has the following beneficial effects:

[0023] 1. The present invention achieves uniform mixing of HE metal salt, titanium precursor and citric acid by regulating the order of adding precursors and the dissolution temperature, heats them to polymerize them, and utilizes the dissolution-polymerization-calcination-nitridation method to prepare high-entropy nitrogen oxide materials. The metal types in the prepared high-entropy nitrogen oxide materials are easily adjustable and have universal applicability.

[0024] 2. The preparation method of the present invention is simple and controllable, and the conditions are mild.

[0025] 3. The high entropy nitrogen oxide material prepared by the present invention has a perovskite structure and a wide spectrum solar energy absorption characteristic. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 XRD characterization of samples prepared in Example 1 and Comparative Example 1;

[0027] Figure 2 The photocatalytic ammonia decomposition and hydrogen production performance of the sample prepared in Example 1. DETAILED DESCRIPTION

[0028] The following is a detailed description of the entire material preparation process through examples, but the scope of the claims of the present invention is not limited by these examples. At the same time, the examples only provide some conditions for achieving this purpose, but do not mean that these conditions must be met to achieve this purpose.

[0029] The materials of Examples 1-10 of the present invention were tested by the following instruments and methods:

[0030] The structural information of the embodiment is analyzed by X-ray diffraction (XRD);

[0031] Examples 1-3 are for adjusting the type and number of metals; Examples 3-5 are for adjusting the polymerization temperature and time; Examples 6-8 are for adjusting the heat treatment temperature and time; Examples 8-10 are for adjusting the nitridation temperature and the time for introducing ammonia.

[0032] Example 1

[0033] (1) 5 mmol of tetrabutyl titanate was dissolved in 12 mL of ethylene glycol, and 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, and Pr(NO3)3 and 20 mmol of citric acid were added to obtain a mixed solution;

[0034] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 130° C. for 6 hours, and cooling to room temperature to obtain a gel precursor;

[0035] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating the mixture to 350° C. at a rate of 5° C. / min in an atmosphere of H2 and Ar, maintaining the mixture for 2 hours, and then heating the mixture to 900° C. after grinding, and maintaining the mixture for 3 hours;

[0036] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 950° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 3 hours to obtain high entropy nitrogen oxide (LaCePrNdSm)TiO2N.

[0037] like Figure 1 As shown, the Ce-based high entropy oxynitride prepared in Example 1 has a single perovskite structure.

[0038] Example 2

[0039] (1) Dissolve 5 mmol of tetrabutyl titanate in 12 mL of ethylene glycol, add 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, Gd(NO3)3 and 20 mmol of citric acid;

[0040] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 130° C. for 6 hours, and cooling to room temperature to obtain a gel precursor;

[0041] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating the mixture to 350° C. at a rate of 5° C. / min in an atmosphere of H2 and Ar, maintaining the mixture for 2 hours, and then heating the mixture to 900° C. after grinding, and maintaining the mixture for 3 hours;

[0042] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 950° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 3 hours to obtain high entropy nitrogen oxide (LaCeSmNdGd)TiO2N.

[0043] Example 3

[0044] (1) 6 mmol of tetrabutyl titanate was dissolved in 12 mL of ethylene glycol, and 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, Pr(NO3)3, and Gd(NO3)3 and 24 mmol of citric acid were added to obtain a mixed solution;

[0045] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 130° C. for 6 hours, and cooling to room temperature to obtain a gel precursor;

[0046] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating the mixture to 350° C. at a rate of 5° C. / min in an atmosphere of H2 and Ar, maintaining the mixture for 2 hours, and then heating the mixture to 900° C. after grinding, and maintaining the mixture for 3 hours;

[0047] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 950° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 3 hours to obtain high entropy nitrogen oxide (LaCeNdPrSmGd)TiO2N.

[0048] Result discussion: Under the premise that other conditions are the same, Examples 1-3 can all prepare high entropy nitrogen oxide materials with a perovskite structure by adjusting the type and amount of metals.

[0049] Example 4

[0050] (1) 6 mmol of tetrabutyl titanate was dissolved in 12 mL of ethylene glycol, and 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, Pr(NO3)3, and Gd(NO3)3 and 24 mmol of citric acid were added to obtain a mixed solution;

[0051] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 110° C. for 18 hours, and cooling to room temperature to obtain a gel precursor;

[0052] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating the mixture to 350° C. at a rate of 5° C. / min in an atmosphere of H2 and Ar, maintaining the mixture for 2 hours, and then heating the mixture to 900° C. after grinding, and maintaining the mixture for 3 hours;

[0053] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 950° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 3 hours to obtain high entropy nitrogen oxide (LaCeNdPrSmGd)TiO2N.

[0054] Example 5

[0055] (1) 6 mmol of tetrabutyl titanate was dissolved in 12 mL of ethylene glycol, and 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, Pr(NO3)3, and Gd(NO3)3 and 24 mmol of citric acid were added to obtain a mixed solution;

[0056] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 160° C. for 3 hours, and cooling to room temperature to obtain a gel precursor;

[0057] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating the mixture to 350° C. at a rate of 5° C. / min in an atmosphere of H2 and Ar, maintaining the mixture for 2 hours, and then heating the mixture to 900° C. after grinding, and maintaining the mixture for 3 hours;

[0058] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 950° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 3 hours to obtain high entropy nitrogen oxide (LaCeNdPrSmGd)TiO2N.

[0059] Result discussion: Under the premise that other conditions are the same, Examples 3-5 can all obtain high entropy nitrogen oxide materials with a perovskite structure by changing the polymerization temperature and time.

[0060] Example 6

[0061] (1) 5 mmol of tetrabutyl titanate was dissolved in 12 mL of ethylene glycol, and 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, and Pr(NO3)3 and 20 mmol of citric acid were added to obtain a mixed solution;

[0062] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 130° C. for 6 hours, and cooling to room temperature to obtain a gel precursor;

[0063] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating it to 300° C. at 5° C. / min in a H2 and Ar mixed gas atmosphere, maintaining it for 3 hours, and then heating it to 1000° C. after grinding, and maintaining it for 1 hour;

[0064] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 900° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 3 hours to obtain high entropy nitrogen oxide (LaCePrNdSm)TiO2N.

[0065] Example 7

[0066] (1) 5 mmol of tetrabutyl titanate was dissolved in 12 mL of ethylene glycol, and 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, and Pr(NO3)3 and 20 mmol of citric acid were added to obtain a mixed solution;

[0067] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 130° C. for 6 hours, and cooling to room temperature to obtain a gel precursor;

[0068] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating the mixture to 350° C. at a rate of 5° C. / min in an atmosphere of H2 and Ar, maintaining the mixture for 2 hours, and then heating the mixture to 600° C. after grinding and maintaining the mixture for 5 hours;

[0069] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 900° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 3 hours to obtain high entropy nitrogen oxide (LaCePrNdSm)TiO2N.

[0070] Example 8

[0071] (1) 5 mmol of tetrabutyl titanate was dissolved in 12 mL of ethylene glycol, and 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, and Pr(NO3)3 and 20 mmol of citric acid were added to obtain a mixed solution;

[0072] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 130° C. for 6 hours, and cooling to room temperature to obtain a gel precursor;

[0073] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating the mixture to 350° C. at a rate of 5° C. / min in an atmosphere of H2 and Ar, maintaining the mixture for 2 hours, and then heating the mixture to 900° C. after grinding, and maintaining the mixture for 3 hours;

[0074] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 900° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 3 hours to obtain high entropy nitrogen oxide (LaCePrNdSm)TiO2N.

[0075] Result discussion: Under the premise that other conditions are the same, Examples 6-8 can all obtain high entropy nitrogen oxide materials with a perovskite structure by changing the heat treatment temperature and time.

[0076] Example 9

[0077] (1) 5 mmol of tetrabutyl titanate was dissolved in 12 mL of ethylene glycol, and 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, and Pr(NO3)3 and 20 mmol of citric acid were added to obtain a mixed solution;

[0078] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 130° C. for 6 hours, and cooling to room temperature to obtain a gel precursor;

[0079] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating the mixture to 350° C. at a rate of 5° C. / min in an atmosphere of H2 and Ar, maintaining the mixture for 2 hours, and then heating the mixture to 900° C. after grinding, and maintaining the mixture for 3 hours;

[0080] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 1200° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 1 hour to obtain high entropy nitrogen oxide (LaCePrNdSm)TiO2N.

[0081] Example 10

[0082] (1) 5 mmol of tetrabutyl titanate was dissolved in 12 mL of ethylene glycol, and 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, and Pr(NO3)3 and 20 mmol of citric acid were added to obtain a mixed solution;

[0083] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 130° C. for 6 hours, and then cooling to room temperature;

[0084] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating the mixture to 350° C. at a rate of 5° C. / min in an atmosphere of H2 and Ar, maintaining the mixture for 2 hours, and then heating the mixture to 900° C. after grinding, and maintaining the mixture for 3 hours;

[0085] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 800° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 5 hours to obtain high entropy nitrogen oxide (LaCePrNdSm)TiO2N.

[0086] Results and Discussion: In Examples 8-10, the formation process of nitrogen oxides was regulated by adjusting the time of introducing ammonia gas and the nitriding temperature under the premise of keeping other conditions the same. Increasing the nitriding time and increasing the nitriding temperature can promote the formation process of nitrogen oxides and improve the crystallinity.

[0087] Comparative Example 1

[0088] 0.6 g of anhydrous sodium carbonate, 1 mmol each of Sm2O3, La2O3, Nd2O3, Ce2O3 and 0.33 mmol of Pr6O 11and 10mmol TiO2, and mixed them evenly by ball milling, with a ball-to-material ratio of 10:1, a rotation speed of 600r / min, and ball milling for 0.5 hours; the obtained mixture was placed in a muffle furnace and calcined at 900℃ for 3 hours, with a heating rate of 5oC / min, and cooled to room temperature, washed with water, and centrifuged to obtain a precipitate, which was dried at 60℃ for 12h; the obtained dried sample was placed in a tube furnace, and in an ammonia atmosphere with a flow rate of 250mL / min, the temperature was raised to 950℃ at 5℃ / min, and maintained for 3 hours to obtain nitrogen oxide (LaCeSmNdPr)TiO x N y .

[0089] Result discussion: Under the same conditions, the molten salt method cannot obtain single-phase perovskite structure nitrogen oxides, indicating that the technology for preparing high-entropy nitrogen oxide materials proposed in the present invention has high purity, mild conditions and simple method.

[0090] Comparative Example 2

[0091] (1) 1 mmol each of La(NO3)3, Ce(NO3)3, Sm(NO3)3, Nd(NO3)3, and Pr(NO3)3 was dissolved in 12 mL of ethylene glycol, and 5 mmol of tetrabutyl titanate and 20 mmol of citric acid were added to obtain a mixed solution;

[0092] (2) placing the mixed solution obtained in step (1) in an oil bath and stirring at 130° C. for 6 hours, and cooling to room temperature to obtain a gel precursor;

[0093] (3) placing the gel precursor obtained in step (2) in a tube furnace, heating the mixture to 350° C. at a rate of 5° C. / min in an atmosphere of H2 and Ar, maintaining the mixture for 2 hours, and then heating the mixture to 900° C. after grinding, and maintaining the mixture for 3 hours;

[0094] (4) The powder obtained in step (3) was placed in a tube furnace, and the temperature was raised to 950° C. at a rate of 5° C. / min in an ammonia atmosphere with a flow rate of 250 mL / min, and maintained for 3 hours to obtain nitrogen oxide [LaCePrNdSm]TiO2N.

[0095] Result discussion: The obtained mixed solution has white precipitate attached, indicating that the present invention can obtain high-purity high-entropy nitrogen oxide material by adjusting the addition order.

[0096] Application Example 1

[0097] The high entropy nitrogen oxide obtained in Example 1 was used as a catalyst material for a photocatalytic ammonia decomposition hydrogen production system, and the photocatalytic ammonia decomposition hydrogen production reaction performance was examined after it was loaded with ruthenium.

[0098] 1. Modification of additives: A high entropy nitrogen oxide with a ruthenium loading of 1 wt%, namely Ru / (LaCePrNdSm)TiO2N, was prepared by an impregnation method. First, the high entropy nitrogen oxide material was impregnated in a solution containing ruthenium chloride, stirred, dried, and ground, and then heated to 300°C in a 5% H2 / Ar atmosphere for 2 h.

[0099] 2. Catalytic performance evaluation: 20 mg Ru / (LaCePrNdSm)TiO2N was coated on a 2*2 cm 2 Ammonia was introduced as the reaction gas, and the temperature was raised to 150°C under visible light (λ>420nm) irradiation. The hydrogen product was detected by gas chromatography to evaluate the ammonia decomposition and hydrogen production performance of the high entropy nitrogen oxide photocatalyst.

[0100] like Figure 2 As shown, the high entropy nitrogen oxide prepared in Example 1 has the ability to photocatalytically decompose ammonia to produce hydrogen under visible light conditions.

[0101] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A method for preparing a Ce-based high entropy oxynitride material, characterized in that: The chemical composition formula of the nitrogen oxide material is HETiO2N, wherein HE is a combination of Ce and at least four of La, Sm, Pr, Nd, Gd, Yb, Tb, Eu, Ho, Er, Tm, Lu, and Dy; the percentage of the molar number of each HE metal element to the total molar number of all HE metal elements is 5% to 35%. The method comprises the following steps: (1) dissolving a titanium precursor in ethylene glycol, adding HE metal salt and citric acid to obtain a mixed solution; (2) heating the mixed solution obtained in step (1) to obtain a gel precursor; (3) heat treating the gel precursor obtained in step (2); (4) The powder obtained in step (3) is nitrided using ammonia gas to obtain the high entropy nitrogen oxide material.

2. The method for preparing the high entropy nitrogen oxide material according to claim 1, characterized in that: In step (1), the molar ratio of citric acid to all metals is 2:1 to 6:1; The molar ratio of ethylene glycol to all metals is 10:1 to 30:1; The molar ratio of the HE metal to Ti is 1:

1.

3. The method for preparing the high entropy nitrogen oxide material according to claim 1, characterized in that: In step (1), the HE metal salt is nitrate, acetate or chloride of HE; The titanium precursor is one of tetrabutyl titanate, tetraisopropyl titanate and tetraethyl titanate.

4. The method for preparing the high entropy nitrogen oxide material according to claim 1, characterized in that: In step (2), the heating temperature is 110 to 160° C., and the insulation time is 3 to 18 hours.

5. The method for preparing the high entropy nitrogen oxide material according to claim 1, characterized in that: In step (3), the heat treatment is firstly heated to 300-350°C, maintained for 1-3 hours, and then heated to 600-1000°C, maintained for 1-5 hours.

6. The method for preparing a high entropy nitrogen oxide material according to claim 1, characterized in that: In step (3), the atmosphere of the heat treatment is hydrogen or a mixture of hydrogen and argon.

7. The method for preparing a high entropy nitrogen oxide material according to claim 1, characterized in that: In step (4), the nitriding temperature is 800 to 1200° C., and the insulation time is 1 to 5 hours.

8. Use of a Ce-based high entropy nitrogen oxide material prepared by the preparation method according to any one of claims 1 to 7 in photocatalysis.

Citation Information

Patent Citations

  • Catalyst and manufacturing method and use therefor

    CA2719313A1

  • Haber-bosch catalyst comprising anion-vacant lattice

    CN112313008A

  • Non-stoichiometric oxynitride nano powder and preparation method thereof

    CN113480316A

  • High-entropy nitrogen oxide material as well as preparation method and application thereof

    CN115770602A

  • Catalyst for catalytically reducing nox

    JP1993261289A

Cited By

  • Ruthenium-based ammonia synthesis catalyst based on high-entropy oxide carrier as well as preparation and application of ruthenium-based ammonia synthesis catalyst

    CN121669226A